2015
DOI: 10.2147/ndt.s82930
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-methyl-d-aspartate receptor encephalitis in a patient with a 7-year history of being diagnosed as schizophrenia: complexities in diagnosis and treatment

Abstract: Anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is a form of autoimmune encephalitis associated with antibodies against the NR1 subunits of NMDARs. Although new-onset acute prominent psychotic syndromes in patients with NMDAR encephalitis have been well documented, there is a lack of case studies on differential diagnosis and treatment of anti-NMDAR encephalitis after a long-term diagnostic history of functional psychotic disorders. The present study reports an unusual case of anti-NMDAR encephalitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
(81 reference statements)
0
4
0
1
Order By: Relevance
“…A 33-year-old woman with anti-NMDAR encephalitis also demonstrated normal EEG [ 8 ]. The previous studies indicated that non-specific findings have been described in EEG [ 10 , 16 ]. So, diagnosis of anti-NMDAR encephalitis remains a challenge according to single laboratory study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 33-year-old woman with anti-NMDAR encephalitis also demonstrated normal EEG [ 8 ]. The previous studies indicated that non-specific findings have been described in EEG [ 10 , 16 ]. So, diagnosis of anti-NMDAR encephalitis remains a challenge according to single laboratory study.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients initially seek help from a psychiatrist, but the disorder is difficult to recognize because psychosis is evident but acute-onset psychiatric episodes are typically absent. Schizophrenia has been reported in several patients who later turned out to have encephalitis [ 10 ]. To our knowledge, only one case has been reported in which the disorder was detected in a patient (16-year-old girl) previously diagnosed with severe depression [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the second comprehensive description of a patient with long-term diagnosis of mania and multiple relapses of psychiatric symptoms, in which the last episode was diagnosed as anti-NMDAR encephalitis. 1 This case is important for several reasons. Firstly, diagnosis was delayed because neuropsychiatric symptoms were attributed to a previously existing, long-standing psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations are variable and sometimes easily misdiagnosed with viral encephalitis [ 39 ], psychosis [ 41 43 ], epilepsy, or other diseases, such as Hashimoto's encephalopathy [ 44 ] and Rasmussen syndrome [ 45 ]. Thus, it is a challenge to the psychiatrists, neurologists, and emergency physicians, as well as gynecologists and oncologists because of the association with teratoma or other tumors.…”
Section: Clinical Manifestationsmentioning
confidence: 99%